Finger displacement in Parkinson disease: up? down? sideways?. (1st May 2014) - Lieberman, Abraham; Dhall, Rohit; Salins, Naomi; Sadreddin, Arshia; Moguel-Cobos, Guillermo; Karis, John; Krishnamurthi, Narayanan
Abstract : We previously reported that patients with tremor preponderant Parkinson disease (PD) displayed upward or lateral displacement of their more tremulous finger when they pointed both their index fingers at a target and closed their eyes for 15 seconds. In this study, we examined the phenomenon in 104 PD patients: 72 patients without tremor and 32 with minimal tremor to see if the displacement is related to the disease or the tremor. Sixty-eight of the 72 patients without tremor, 94%, exhibited finger displacement suggesting the phenomenon is related to the disease. None of the 104 patients were demented: mini-mental status examination (MMSE) score 29.0 ± 0. 75. Ninety patients displayed upward displacement (56 patients) or lateral or medial displacement (34 patients). MMSE score of the 90 patients: 29.2 ± 0.74 with no score < 28. Eight patients (6 without tremor) displayed downward displacement. MMSE score of the 8 patients: 27.5 ± 0.35 with 5 having MMSE score of 27. Although not significant the results suggest that patients with downward displacement and lower MMSE score may be evolving a dementia. Upward displacement with eyes closed for 15 seconds requires an ability to "remember" the position of the finger in space and to alter tone to overcome gravity. Downward displacement implies an inability to "remember" the position of the finger in space an inability to overcome the effects of gravity. This may be more likely in patients who are evolving a dementia. Two patients, with PD-like symptoms, and specific anatomical abnormalities are also presented as they illustrate the anatomy of finger displacement.